Polymorphic modifications of a 1H‐pyrrolo[3, 2, 1‐ij]quinoline‐5‐carboxamide possessing strong diuretic properties. Issue 12 (27th November 2018) - Shishkina, Svitlana V.; Levandovskiy, Igor A.; Ukrainets, Igor V.; Sidorenko, Lyudmila V.; Grinevich, Lina A.; Yanchuk, Igor B.
Abstract : Two polymorphic modifications of 6‐hydroxy‐ N ‐(4‐methoxyphenyl)‐4‐oxo‐2, 4‐dihydro‐1 H ‐pyrrolo[3, 2, 1‐ ij ]quinoline‐5‐carboxamide possessing strong diuretic properties have been studied comprehensively. Differences in the crystal packing have been analyzed using a method based on a comparison of pairwise interaction energies in the crystal phase. Abstract : 6‐Hydroxy‐ N ‐(4‐methoxyphenyl)‐4‐oxo‐2, 4‐dihydro‐1 H ‐pyrrolo[3, 2, 1‐ ij ]quinoline‐5‐carboxamide, C19 H16 N2 O4, possesses strong diuretic properties and can be used as a new hypertension remedy. Two polymorphic modifications of this compound have been found, namely the triclinic polymorph (space group P ), with one molecule in the asymmetric unit, and the monoclinic polymorph (space group P 21 / n ), with two molecules in asymmetric unit. An analysis of the pairwise interaction energies between the molecules in the crystal phase revealed differences in the crystal packing. The triclinic form has only one level of organization, namely a chain/column, while the monoclinic form has two levels of organization, with a chain/column as the primary basic structural motif and a layer as the secondary basic structural motif.